L'image de L'enfant et de L'enfance dans "L'emile de Rousseau" - الحبشي، هشام بن محمد (جامعة الملك عبدالعزيز, 2021)
تتكون دراسة صورة الطفل في كتاب Emile للفيلسوف الفرنسي روسو أولًا وقبل كل شيء من إثارة الجدل الكبير حول التعليم الذي نشأ في النصف الثاني من القرن السابع عشر. يتكون أساسًا من دراسة خصوصية الطفولة في عمل روسو، وبأي وسيلة تتجلى. وهي تتمثل في إظهار أهمية الحاكم والطبيعة، والدور الذي يلعبونه فيما يتعلق بتعليم إميل، وفيما يتعلق بصورة الطفل بشكل عام. شهد القرن الثامن عشر إنتاجًا هامًا للكتابات المتعلقة بالتعليم، خاصة بعد عام 1750. إن ظهور هذه الأدبيات يفسر من ناحية أخرى بأهمية موضوع التعليم. يشتمل هذا الموضوع على العديد من المناقشات حول الطفولة، والتعليم، .... حالة الطفل، ودور الأب، وما إلى ذلك. أدت إلى الكثير من التفكير، وألهمت عددًا كبيرًا من المؤلفين والفلاسفة. ثم في عام 1762، ترك طرد المتدينين فراغًا كبيرًا في المشهد التعليمي الفرنسي، وأظهر الحاجة، وحتى الضرورة الملحة، لتطوير أساليب جديدة ونظريات تعليمية جديدة. ومن ثم فإن العديد من الفلاسفة سيهتمون بمشاكل دقيقة للغاية: التكوين النفسي للأفراد، و"نفسية الطفل"، العلاقة الموجودة بين الطفل والبالغ "الأب". قبل مناقشة الاتجاهين الرئيسيين في النقاش التربوي، سيكون من الضرورة دراسة تعريف فإن العديد من الفلاسفة سيهتمون بمشاكل دقيقة للغاية: التكوين النفسي للأفراد، و"نفسية الطفل"، العلاقة الموجودة بين الطفل والبالغ "الأب". قبل مناقشة الاتجاهين الرئيسيين في النقاش التربوي، سيكون من الضروري دراسة تعريف كلمتي الأب والطفل في هذه الدراسة.
Studying the image of the child in Rousseau's Emile consists first in evoking the great debate on education, which arose in the second half of the XVIIth century. It mainly consists in studying the specificity of childhood in Rousseau's work, and by what means it manifests itself. It consists in showing the importance of the governor and of nature, and the role they play in relation to Emile's education, and in relation to the image of the child in general. The XVIIIth century saw an important production of writings on education, especially after 1750. The appearance of this literature explained on the one hand by the importance of the subject of education; this subject engages several debates on childhood, education, the status of the child, the role of the father, etc. On the other hand, as J.M. DOLLE emphasizes, the appearance of Montesquieu's work, L'Esprit des Lois, has given rise to much reflection, and has inspired a large number of authors and philosophers. Then in 1762, the expulsion of the Jesuits left a great void in the French educational landscape, and showed the need, even the urgency, to develop new methods and new educational theories. It is thus that many philosophers will be interested in very precise problems: the formation of the citizen, the "psychology of the child", the relation which exists between the child and the adult "father or governor". Before discussing the two main trends in the education debate, it will be necessary to study the definition of the words father and child in the dictionary of the Encyclopedia of the time.
Keywords: الفلسفة الغربية -- التكوين النفسي -- التنشئة الاجتماعية -- روسو، جان جاك، ت. 1778 م